Implementasi Good Governance di Kecamatan Pasan Kabupaten Minahasa Tenggara - Rondonuwu, Andre; Rompas, Welson Yappi; Pombengi, Jericho Denga (Sam Ratulangi University, 2015)
ABSTRAK : Sub-district is the district / city that has an important position and role in the framework of theeffectiveness of the regional administration, so it must be able to effectively implement good governance.Accordingly, the study is intended to answer the question